Efficacy and mechanism of high-purity HAMCC combined with CGF in promoting the repair of radiation-induced skin and soft tissue damage - Xiaohao Hu; Anru Liang; Tongling Zhao; Yu Ling; Yanlin Wei; Yuer Zuo; Hongmian Li (PLoS ONE, 2025)
Radiotherapy, a prevalent and effective treatment for various malignancies, often causes collateral damage to normal skin and soft tissues in the irradiated area. To address this, we developed a novel approach combining SVFG-modified adipose-derived high-activity matrix cell clusters (HAMCC) with concentrated growth factors (CGF) to enhance regeneration and repair of radiation-induced skin and soft tissue injuries. Our study included cellular assays, wound healing evaluations, and histological analyses. In the inflammatory wound healing environment, this treatment reduced ROS and 8-oxo-dG expression while increasing four antioxidant-related proteins (Nrf2, HO-1, NQO1, AKR1C1), thereby suppressing oxidative stress and improving wound healing efficiency. Additionally, the HAMCC and CGF combination promoted collagen expression and rearrangement and accelerated angiogenesis. This innovative treatment presents a promising strategy for regenerating and repairing radiation-induced skin and soft tissue damage.